Análise da proposta educacional das escolas metodistas - Schroeder, Edni Oscar (1982)
The aim of this paper is to analyze the educational proposal of the Methodist Schools from the point of the relationship between them and the Methodist Church itself as well as the Brazilian society as a whole, at the time when Brazil was defined as a dependent capitalist country. Through the research and analysis of regulations, prospects, year books, teaching programs, curricular organization, educational reviews, articles, speeches, file documents and so on, taken from 'Instituto Porto Alegre' (IPA) as the reference to interpret the educational proposal of the Methodist Schools, were detected the basic principles of the referred proposal since the School foundation (1919) up to the present time. An analysis of the historical evolution of the Methodist Church and Schools, always considering a former relationship with the United States of America (hegemonial nation, external) and later on with the Brazilian State (internal dominion), was proceeded. To close up, as the Brazilian society was being strutured as definite principles and purposes by a hegemonial nation (United States) and as the Brazilian State was being organized as agent of an internal dominion, the Methodist Schools passed from an external dependent level to an internal dependent level, and the relative success of their educational proposal faded with the implantation of the oficial teaching system in the country.